454 Effects of Human Brain Organoid Age on Post-Transplant Growth in the Rat Motor Cortex. (April 2023) - Blue, Rachel; Fu, Marissa; Harary, Paul; Jgamadze, Dennis; Rahaman, Imon; Singh, Shikha; Ming, Guo-Li; Song, Hongjun; Chen, H. Isaac
Abstract : INTRODUCTION: Human brain organoids have potential to be used as a substrate for brain repair following injury, however the factors affecting survival and integration of transplanted organoids are unknown. We hypothesized that organoids transplanted at an earlier time point would result in improved survival and integration into the motor cortex because of their greater growth potential. METHODS: Human forebrain organoids at two timepoints (d20-25, d55-60) were transplanted into the motor cortex of adult rats following an aspiration injury. The first cohort was survived for 1 month post transplantation (MPT, n = 6); the second cohort was survived for 2 MPT (n = 16). Quantification of organoid volume and immunohistochemistry were performed. RESULTS: Survival of organoids post-transplantation was >90%. Pre-transplantation organoid size at d20-25 was significantly smaller than d55-60 (p < 0.0001). Average organoid volume 2 MPT was 1.04E + 10 µm 3, significantly increased from 1435.4 µm 3 pre-transplant (p = 0.0156). 2 MPT was correlated with more growth than 1MPT, though not statistically significant (p = 0.2672). Younger organoids trended toward a larger end-volume with the mean d20-25 volume being 3.1x larger than d55-60 at 1MPT (p = 0.3211) and 1.74x larger at 2MPT (p = 0.5090). Axon projections were seen in the adjacent host cortex at both timepoints. Both organoid age groups contained neural progenitors (PAX6, Sox2) with d20-25 retaining areas reminiscent of neural progenitor zones at 1MPT. CONCLUSIONS: Survival of transplanted organoids following injury was successful with a vast majority of organoids experiencing rapid growth within the injury cavity. Both age cohorts demonstrated adjacent axon projection and the presence of neural progenitors. Though further investigation is needed to clarify the influence of organoid maturity on integration, the survival rate and degree of post-transplant growth is a promising first step.